Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/polym15071771
|View full text |Cite
|
Sign up to set email alerts
|

Tremella fuciform Polysaccharides: Extraction, Physicochemical, and Emulsion Properties at Different pHs

Abstract: The chemical composition, macromolecular characteristics, and structure of four types of Tremella fuciform polysaccharides (TPS) were analyzed, including one TPS that was extracted in the laboratory (L-TPS) and three commercial TPS. The effects of pH on the properties of TPS emulsions were investigated by analyzing their zeta potential, particle size, apparent viscosity, and stability. The results showed that L-TPS presented a higher percentage content of protein (2.33%) than commercial TPS (0.73–0.87%), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…Research has demonstrated that the emulsifying properties of TP depend on its molecular characteristics, including molecular weight, monosaccharide composition, and protein content [9]. Polysaccharides with a high protein content and low molecular weight exhibit emulsifying activity well, while those with a high molecular weight demonstrated superior emulsification stability [10]. Additionally, Foods 2024, 13, 1545 2 of 15 electrostatic repulsion and viscosity play a crucial role in maintaining the stability of the emulsion system [7].…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that the emulsifying properties of TP depend on its molecular characteristics, including molecular weight, monosaccharide composition, and protein content [9]. Polysaccharides with a high protein content and low molecular weight exhibit emulsifying activity well, while those with a high molecular weight demonstrated superior emulsification stability [10]. Additionally, Foods 2024, 13, 1545 2 of 15 electrostatic repulsion and viscosity play a crucial role in maintaining the stability of the emulsion system [7].…”
Section: Introductionmentioning
confidence: 99%